Organizing empyema induced in mice by Streptococcus pneumoniae: effects of plasminogen activator inhibitor-1 deficiency - Tucker, Torry A. (Clin Transl Med, 2016)
BACKGROUND: Pleural infection affects about 65,000 patients annually in the US and UK. In this and other forms of pleural injury, mesothelial cells (PMCs) undergo a process called mesothelial (Meso) mesenchymal transition (MT), by which PMCs acquire a profibrogenic phenotype with increased expression of α-smooth muscle actin (α-SMA) and matrix proteins. MesoMT thereby contributes to pleural organization with fibrosis and lung restriction. Current murine empyema models are characterized by early mortality, limiting analysis of the pathogenesis of pleural organization and mechanisms that promote MesoMT after infection. METHODS: A new murine empyema model was generated in C57BL/6 J mice by intrapleural delivery of Streptococcus pneumoniae (D39, 3 × 10(7)–5 × 10(9) cfu) to enable use of genetically manipulated animals. CT-scanning and pulmonary function tests were used to characterize the physiologic consequences of organizing empyema. Histology, immunohistochemistry, and immunofluorescence were used to assess pleural injury. ELISA, cytokine array and western analyses were used to assess pleural fluid mediators and markers of MesoMT in primary PMCs. RESULTS: Induction of empyema was done through intranasal or intrapleural delivery of S. pneumoniae. Intranasal delivery impaired lung compliance (p < 0.05) and reduced lung volume (p < 0.05) by 7 days, but failed to reliably induce empyema and was characterized by unacceptable mortality. Intrapleural delivery of S. pneumoniae induced empyema by 24 h with lung restriction and development of pleural fibrosis which persisted for up to 14 days. Markers of MesoMT were increased in the visceral pleura of S. pneumoniae infected mice. KC, IL-17A, MIP-1β, MCP-1, PGE(2) and plasmin activity were increased in pleural lavage of infected mice at 7 days. PAI-1(−/−) mice died within 4 days, had increased pleural inflammation and higher PGE(2) levels than WT mice. PGE(2) was induced in primary PMCs by uPA and plasmin and induced markers of MesoMT. CONCLUSION: To our knowledge, this is the first murine model of subacute, organizing empyema. The model can be used to identify factors that, like PAI-1 deficiency, alter outcomes and dissect their contribution to pleural organization, rind formation and lung restriction.